E-COMMERCE IN POLAND AND UKRAINE: DEVELOPMENT AND CHALLENGES - Levytska, Svitlana; Demianiuk, Regina (Management and Administration Journal, 2024)
The aim of this article is to examine and explore the characteristic features of e-commerce, as well as to show the possibilities and alternatives for the further development of e-commerce in Poland and Ukraine. The article discusses, among others, the advantages of e-commerce, and the approaches towards its service. It also considers the dynamics of e-commerce development in Poland and Ukraine in recent years, the positive consequences of e-commerce expansion in terms of trade turnover, as well as the range of goods and services; and, in turn, thedevelopment of online stores. The authors, after analysing the source materials relating to e-commerce sector inneighbouring countries, state that on-line trade has a demand among people and that there are perspectives of furtherdevelopment even in difficult conditions of martial law in Ukraine. According to presented assessments, the importanceof online shopping in Poland is increasing, online shopping is gaining new customers in various age groups, theopenness of Polish e-customers to cross-border shopping is growing and more and more sellers are deciding to sellonline. In Ukraine online trade is gaining momentum and its development has created the conditions for Ukrainianenterprises to integrate with the European digital space. The article proposes alternative ways for improving normativeregulation in terms of the development of e-commerce in Ukraine under the conditions of compliance with faircompetition. Polish and Ukrainian e-commerce market faces a number of challenges and tasks and theirimplementation will enable the achievement of higher global standards.